Residual level of Chromium, Copper and Manganese in Soil and Water of N-24 Parganas (West Bengal) and its Relation to Chevon quality - Mahapatra, G.; Biswas, S.; Bhattacharya, D.; Patra, G. (International Journal of Bio-resource and Stress Management, 2019)
An increase in human population coupled with urbanization, has resulted for higher demand in meat per capita.Meat and meat products are important for human diet as they provide a great part of nutrients, including necessary trace elements which act as micronutrients. The present study focuses on the concentration of trace elements (chromium, copper and manganese) in the meat of goats (40 weeks age) reared in the three targeted zones of West Bengal, where high heavy metal concentrations in soil and water is a matter of concern. Soil, water and chevon samples were collected from three targeted zones of West Bengal.The meat samples were taken from free range goats grazing locally. Over a span of six months samples were collected, digested and analyzed by atomic absorption spectrophotometry. The mean values of heavy metals in soil samples ranged from 29.96-49.260 ppm of chromium, 14.65 to 38.3 ppm for copper and 198.6 to 482 ppm for manganese. The mean values of heavy metals in water ranged from 0.006-0.02 ppm for chromium, 0.0024 to 0.0180 ppm for copper and 0.068 to 0.436 ppm for manganese . Soil samples revealed high concentration of chromium and copper whereas water samples revealed high concentration of manganese. These levels did not impact the edible quality of meat. Hence advocating that risks associated with chevon consumption from goats (40 weeks age) reared in areas having high heavy metal residual content are negligible and consumption of such meats should not necessarily cause any dilemma.